Assessment of changes in the threadfin bream species composition using Markov chain - Vivekanandan, E; Venugopalan, R; Ramadoss, P (Indian Journal of Fisheries, 2011)
The threadfin bream landings in the Chennai Fisheries Harbour consistently declined from 5450 t in 1994 to 2406 t in ’98. The catch rate also declined from 22.6 kg/trawl hour in ’90 to 2.3 kg/h in ’98. Markovian model is employed to assess the changes in species dominance over the 15 year period. Transition probabilities as well as the steady state probabilities are worked out separately for four species of threadfin breams. It was found that the probability of dominance of Nemipterus japonicus has decreased, indicating a major shift in the species composition of the threadfin breams. The possibility of short term prediction on the species dominance pattern by employing Markovian model is demonstrated.